Dirty Stacks, High Stakes : An Overview of Brick Sector in South Asia - Eil, Andrew; Li, Jie; Baral, Prajwal; Saikawa, Eri (World Bank, Washington, DC, 2020)
This report surveys the brick kiln sector in three South Asian countries: Bangladesh, India, and Nepal, with particular focus on experiences and lessons learnt from Bangladesh, where data and information on the brick kiln industry and market conditions are most extensive, and where engagement of the donor community has been most consistent and widespread.